Trauma and Gene Expression: Understanding the Connections. (3rd March 2020) - Pilkay, Stefanie Renee; Combs-Orme, Terri
Abstract: Over 60% of trained social workers provide mental health services in their practices, and in all these settings clients are likely to have experienced trauma influencing their current circumstances, including childhood maltreatment and neglect. The 1998 Adverse Childhood Experiences Study has heightened interest in the long-term effects of trauma, especially early in life. Research has shown that our experiences influence our genes' activity through biochemical changes in what is known as epigenetic marks. Yet social work practice has participated minimally in targeting the influences of genes on behavior for research or intervention, partially because of a lack of scientific knowledge. This systematic review examines published research that investigated the influences of early trauma experiences on changes in gene expression related to emotionality and stress response. Authors conducted a systematic literature review according to the steps outlined by Shuster in Google Scholar, PubMed, and PsycINFO. Collected literature was reduced to 76 peer-reviewed articles after applying exclusion criteria. A strong pattern of relationships emerged from the review. Trauma and early life stress were associated with epigenetic marks in offspring on genes linked to stress reactivity (22 studies) and emotionality (23 studies).